2020
DOI: 10.1021/acs.joc.9b02505
|View full text |Cite
|
Sign up to set email alerts
|

A Sulfonium Triggered Thiol-yne Reaction for Cysteine Modification

Abstract: We report a facile thiol-yne type reaction triggered by the sulfonium center. After facile propargylation of thiolethers, the resulting sulfonium could undergo facile addition with thiols in aqueous media at ambient temperature. Further applying this reaction in unprotected peptides bearing neighboring methionine and cysteine could enable a facile intramolecular addition to construct cyclic peptides with better stability, good glutathione resistance, and increased cellular uptakes. Also, the propargylated sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 54 publications
0
29
1
Order By: Relevance
“…These efforts have been extensively reviewed [1–5] . More recently, several more of these methods have been reported that utilize novel functional groups to demonstrate impressive chemoselectivity to Cys, [6–9] Lys, [10–13] His, [14–16] Met, [17–19] Trp, [20] and Tyr [21] …”
Section: Overview Of Protein Modification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These efforts have been extensively reviewed [1–5] . More recently, several more of these methods have been reported that utilize novel functional groups to demonstrate impressive chemoselectivity to Cys, [6–9] Lys, [10–13] His, [14–16] Met, [17–19] Trp, [20] and Tyr [21] …”
Section: Overview Of Protein Modification Methodsmentioning
confidence: 99%
“…These efforts have been extensively reviewed. [1][2][3][4][5] More recently, several more of these methods have been reported that utilize novel functional groups to demonstrate impressive chemoselectivity to Cys, [6][7][8][9] Lys, [10][11][12][13] His, [14][15][16] Met, [17][18][19] Trp, [20] and Tyr. [21] Relatedly, dehydroalanine (Dha)-mediated modification is an indirect but notable approach.…”
Section: Functional Group Innate Reactionsmentioning
confidence: 99%
“…133 In the following experiment, Li lab reported another facile thiolyne reaction triggered by sulfonium center and translated it into the synthesis of stapled peptides. 134 The peptide bearing i, i+4 Met-Cys paired residues was used as the linear precursor, which could undergo robust propargylation at Met residue. And then the resulting sulfonium could couple with another Cys residue with satisfying functional group tolerance, thus constructing the stapled peptides with increased serum stability, good GSH resistance, and enhanced cellular uptakes compared to the linear peptides (Scheme 15B).…”
Section: Met-cys Via Chemo-selective Bis-alkylationmentioning
confidence: 99%
“…And then the resulting sulfonium could couple with another Cys residue with satisfying functional group tolerance, thus constructing the stapled peptides with increased serum stability, good GSH resistance, and enhanced cellular uptakes compared to the linear peptides (Scheme 15B). 134 2.9. His-His via Metal Chelates…”
Section: Met-cys Via Chemo-selective Bis-alkylationmentioning
confidence: 99%
“…On the other hand, thionium is an important intermediate state of Pummerer-type reactions, which is highly active substrates in nucleophilic S E Ar reactions [48][49][50][51][52][53] . Recently, our group developed various sulfonium-based chemistry for bioorthogonal applications with excellent biocompatibility [54][55][56] . Thus, we considered the application of electrophilic thionium intermediates for protein modification.…”
Section: Introductionmentioning
confidence: 99%